Role and Performance Evaluation of NFRA as Independent Regulator - A Case Departing Power or Conflict with ICAI - Dr. Chandan Karki (International Journal of Engineering and Management Research, 2023)
The National Financial Reporting Authority (NFRA) constituted on 01 October 2018 under section 132 of the Companies Act, 2013 with the objective of constituting independent regulator for the auditing function to improve the transparency and reliability of the financial statements. The ICAI is set up under the The Institute of Chartered Accountant Act 1949 with the entrusted task of formulating accounting and auditing standards in India. The objective of the paper to examine the role and performance of NFRA in the light of the presence of ICAI as existing monitoring body of accounting and auditing profession. The paper analysed the cases and reports submitted in the recent past by both the regulatory body. The gross violations of the accounting and auditing standards reported by NFRA are the eye opener. The paper concludes that the two body should work together to evolve improving quality of accounting and auditing standards in practice in India. The judgment of the Hon’ble Supreme Court of India in S.Sukumar VS The secretary, also emphasized an independent body to regulate and oversee the profession in the best interest of the resources and current global practices.